Historic Cimarron self guided tour version 2 (Cimarron, NM Cimarron Historical Society)
This handout is about the local history and points of interest for the City of Cimarron, NM.
Leaflet - Handout
Mater List Item # 22
File location is in the New Mexico File Cabinets
Keywords: Maxwell, Lucien B. -- 1818-1875; Carson, Kit -- 1809-1868; Bent, Charles; Vrain, Ceran St; Owens, Richard; Wooton, Dick (Uncle); Beaubien, Charles; Fremont, John Charles; Menard, Pierre; Miranda, Guadalupe; Beaubien, Carlos; Maxwell, Luz Beaubien; Springer, Frank -- 1848-1927; Lambert, Henry; Old Aztec Mill; Maxwell Ranch; C S Cattle Company; Cimarron Historical Society; CS Ranch; CS Cattle Co; St. James Hotel; Wooton's Toll Gate; Town History; Town Maps; Tour Guides; Maxwell Land Grant; Beaubien-Miranda Grant; Origin Story; Cimarron, New Mexico